PEMBANGUNAN SOSIAL DI NEGARA MAJU DAN BERKEMBANG - Edi Suharto (Politeknik Kesejahteraan Sosial, 2003)
Social Development in Developed and Less Developed Countries.Social development can be seen in oconomic ability (GDP) and Government expenditure on education, health and social security sectors. Related to the inputindicators, there are someopinions that social development would not worked without high economic ability, and only some wealth states enable to conduct the social investment. By showing data of GDP level and government expenditures on social development sectors, the writer categorising four state models regarding their commitment on social development. The study have tried to respond hypothesis that followed by community, polliticiants, academicians, that social development is expensive and W1able to be conducted by developing countries.